Ordinamento di emergenza sanitaria e il suo impatto sul sistema d’istruzione pubblica (Società e diritti, 2021)
AbstractIn the context of an existing emergency system, the rules laid down by the Dpcms, on the basis of decrees-laws of the Government, are to be considered not an expression of regulatory power but an expression of the power of ordinance; power anchored to the principle of legality and shared by a plurality of apical subjects of public administration: ministers, President of the regional government, mayors, prefects, civil protection